2017
DOI: 10.1183/13993003.00711-2017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erdosteine on the rate and duration of COPD exacerbations: the RESTORE study

Abstract: Oxidative stress contributes to chronic obstructive pulmonary disease (COPD) exacerbations and antioxidants can decrease exacerbation rates, although we lack data about the effect of such drugs on exacerbation duration.The RESTORE (Reducing Exacerbations and Symptoms by Treatment with ORal Erdosteine in COPD) study was a prospective randomised, double-blind, placebo-controlled study, enrolling patients aged 40–80 years with Global Initiative for Chronic Obstructive Lung Disease stage II/III. Patients received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 32 publications
5
106
0
8
Order By: Relevance
“…Erdosteine is currently the only mucolytic/antioxidant agent that has been evaluated in patients with frequent exacerbations, those that have experienced two or more COPD exacerbations requiring medical intervention in the previous 12 months. The recent Reducing Exacerbations and Symptoms by Treatment with ORal Erdosteine in COPD (RESTORE) study [13], which enrolled 445 frequent exacerbators,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Erdosteine is currently the only mucolytic/antioxidant agent that has been evaluated in patients with frequent exacerbations, those that have experienced two or more COPD exacerbations requiring medical intervention in the previous 12 months. The recent Reducing Exacerbations and Symptoms by Treatment with ORal Erdosteine in COPD (RESTORE) study [13], which enrolled 445 frequent exacerbators,…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained from 1,278 patients (52.66% in the active treatment group, 47.34 in the control group) were selected from 10 published studies, including 6 studies on chronic bronchitis [26][27][28][29][30][31], 3 studies on COPD [12,13,32], and 1 study on patients suffering from both chronic bronchitis and COPD [33]. Eight studies had a Jadad score ≥3 [12, 13, 26-29, 31, 32], and 2 studies had a Jadad score <3 [30,33].…”
Section: Studies Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Many patients with COPD are older or have comorbid conditions that can be associated with renal or hepatic impairment. 2,3 Revefenacin is a once-daily, long-acting, lung-selective muscarinic receptor antagonist formulated as a nebulized inhalation solution for use with a standard jet nebulizer for treatment of patients with COPD. Nebulized therapies are of particular interest in patients with poor hand/breath coordination and/or respiratory muscle weakness that limits their use of dry powder inhalers and pressurized metered-dose inhalers.…”
Section: Introductionmentioning
confidence: 99%
“…The active metabolites of erdosteine exhibit mucolytic and free radical scavenging activity [10] and previous small clinical trials have suggested some benefit in treating acute exacerbations of COPD with erdosteine [11,12]. In this issue of the European Respiratory Journal, DAL NEGRO et al [13] report results from a Phase-III controlled clinical trial that enrolled patients with GOLD stage II-III COPD and randomised them to receive erdosteine (300 mg twice daily) or a placebo for 12 months in addition to their usual COPD therapy. The primary outcome was the number of acute exacerbations (mild, moderate or severe) during the study.…”
mentioning
confidence: 97%